The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1080/14786410500218591
|View full text |Cite
|
Sign up to set email alerts
|

Lignans fromArnicaspecies† ‡

Abstract: From four Arnica species (A. angustifolia Vahl ssp. attenuata (Greene) Maguire, A. lonchophylla Greene ssp. lonchophylla Maguire (flowerheads), A. chamissonis Less. ssp. foliosa (Nutt.) Maguire, A. montana L. (roots and rhizomes)) a total of twelve lignans of the furofuran-, dibenzylbutyrolactone- and dibenzylbutyrolactol-type were isolated. No report on lignans as constituents of Arnica species exists so far. Besides the known pinoresinol, epipinoresinol, phillygenin, matairesinol, nortrachelogenin and nortra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…All the above data suggested 1 was a sesquiterpenoid. Comparison of the 13 C-NMR data of 1 with those of the known compound (3R,4aS,8aR)-3,4,4a,8a-tetrahydro-6-hydroxy-5,8a-dimethyl-3-(1-methylethenyl)-1,7-naphthalenedione 10) displayed that most of the 13 C-NMR signals of the two compounds were almost same, except the signals at δ C 54.4 (C-8a), 32.0 (C-8), 27.1 (C-12) and 10.8 (C-13) in 1 had a few differences from the signals of δ C 49.7, 29.3, 24.4, 13.9 in the compared compound, suggesting that C-8a, C-8, C-12 and C-13 did not have the same chemical environment as the compared compound. The H correlation spectroscopy (COSY) cross-peaks of H-8a (δ H 2.66)/H-8 (δ H 3.01), H-3 (δ H 1.60)/H-2 (δ H 2.29) and H-4 (δ H 2.21), and the heteronuclear multiple bond connectivity (HMBC) correlations from H-12 (δ H 1.36) to C-8a (δ C 54.4), C-4a (δ C 42.9), C-4 (δ C 42.1) and C-5 (δ C 129.6), indicated that a methyl (C-12) was connected to C-4a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the above data suggested 1 was a sesquiterpenoid. Comparison of the 13 C-NMR data of 1 with those of the known compound (3R,4aS,8aR)-3,4,4a,8a-tetrahydro-6-hydroxy-5,8a-dimethyl-3-(1-methylethenyl)-1,7-naphthalenedione 10) displayed that most of the 13 C-NMR signals of the two compounds were almost same, except the signals at δ C 54.4 (C-8a), 32.0 (C-8), 27.1 (C-12) and 10.8 (C-13) in 1 had a few differences from the signals of δ C 49.7, 29.3, 24.4, 13.9 in the compared compound, suggesting that C-8a, C-8, C-12 and C-13 did not have the same chemical environment as the compared compound. The H correlation spectroscopy (COSY) cross-peaks of H-8a (δ H 2.66)/H-8 (δ H 3.01), H-3 (δ H 1.60)/H-2 (δ H 2.29) and H-4 (δ H 2.21), and the heteronuclear multiple bond connectivity (HMBC) correlations from H-12 (δ H 1.36) to C-8a (δ C 54.4), C-4a (δ C 42.9), C-4 (δ C 42.1) and C-5 (δ C 129.6), indicated that a methyl (C-12) was connected to C-4a.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15] Oxidant stress plays an important role in the pathogenesis of many cardiovascular diseases (CVDs), and the use of antioxidant supplements is very benefit to the prevention of coronary artery diseases. 16) Due to the bioactivity of S. pinnatifolia related to the cardiovascular system, all the lignans isolated from this plant in our present studies were tested for their anti-oxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…This is an attractive plant species for the pharmaceutical industry, as it contains numerous pharmacologically active substances and is characterised by similarity of pharmacological effects to A. montana (Willuhn et al, 1983;Leven and Willuhn, 1987;Nichterlein, 1995). Moreover, A. chamissonis is a good source of bioactive compounds (Leven and Willuhn, 1987;Merfort and Wendisch, 1987;Roki et al, 2001;Schmidt et al, 2006;Gawlik-Dziki et al, 2009), a valuable source of herbal raw material and a pharmaceutical substitute for the endangered mountain arnica (Willuhn, 1998;Cassell et al, 1999;Sugier and Gawlik-Dziki, 2009;Gawlik-Dziki et al, 2011). A. chamissonis extracts exhibit potent antiinflammatory and antiradical activity and possesses high antioxidant abilities that might be helpful in preventing or slowing the progress of free radical-dependent diseases (Cassell et al, 1999;Gawlik-Dziki et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Its pharmacological value is due to the presence of sesquiterpene lactones, flavonoids, essential oils, and other active compounds in various parts of the plant. The roots contain essential oils, phenolic acids, oligosaccharides, lignans, etc (Willuhn, 1972a(Willuhn, , 1972bRossetti et al, 1984;Schmidt et al, 2006;Pljevljaušić et al, 2012). The chemical composition of hairy roots of A. montana obtained by genetic transformation of plant tissue with Agrobacterium rhizogenes is less studied.…”
Section: Introductionmentioning
confidence: 99%